Fuzzy Logic Approach to Identify Deprivation Index in Peninsular Malaysia - Muhammad Azam Haris Che Amat; Syibrah Naim; Syerrina Zakaria (Bulletin of Electrical Engineering and Informatics, 2018)
Deprivation indices are similar to inequalities index or index of disadvantageous. It was built to measure the basic necessities in a specific study area or region. There were many indices that have been constructed in the previous study. However, since these indices had depended mostly on two factors; socio-economic conditions and geography of the study area, thus different result would be generated in different areas. The objective of this study is to construct the new index based on above factors in Peninsular Malaysia by using a fuzzy logic approach. This study employed twelve variables from different facilities condition that was obtained from Malaysia 2000’s census report. These variables were considered as input parameters in the fuzzy logic system. Data turned into linguistic variables and shaped into rules in the form of IF-ELSE conditions. After that, the centroid of area method is applied to acquire the final deprivation index for a specific district in Peninsular Malaysia. The result showed that less developed states generated lower index for examples Kelantan and Kedah while more developed states generated a higher index for examples Selangor and W.P. Kuala Lumpur.